2020
DOI: 10.1007/s11426-019-9671-0
|View full text |Cite
|
Sign up to set email alerts
|

Chapter model systems in heterogeneous catalysis at the atomic level: a personal view

Abstract: The review presents an overview of studies in the surface science of oxide and related surfaces with an emphasis of the studies performed in the authors' group. Novel instruments and technique developments, as well as their applications are reported, in an attempt to cover studies on model systems of increasing complexity, including some of the key ingredients of an industrially applied heterogeneous catalyst and its fabrication. The review is intended to demonstrate the power of model studies in understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 144 publications
(217 reference statements)
0
10
0
Order By: Relevance
“…Combined studies on model systems with different levels of complexity have been demonstrated to be an effective strategy towards af undamental understanding of complex systems. [14] Herein,w er eport a comprehensive experimental study of H 2 interaction with welldefined CeO 2 (111)t hin films and CeO 2 powders in wide range of temperatures and pressures, combinedwith DFT calculations of CeO 2 (111)s urfaces with oxygen vacanciesa tt he surface and in the bulk. We provide spectroscopice videncef or the interplay between hydroxyl and hydride formation within the bulk, and connectt hose resultst ot he evidencep resented for the corresponding species on the surface and in the near surface region, allowing us to reach ac onsistent picture.…”
Section: Introductionmentioning
confidence: 99%
“…Combined studies on model systems with different levels of complexity have been demonstrated to be an effective strategy towards af undamental understanding of complex systems. [14] Herein,w er eport a comprehensive experimental study of H 2 interaction with welldefined CeO 2 (111)t hin films and CeO 2 powders in wide range of temperatures and pressures, combinedwith DFT calculations of CeO 2 (111)s urfaces with oxygen vacanciesa tt he surface and in the bulk. We provide spectroscopice videncef or the interplay between hydroxyl and hydride formation within the bulk, and connectt hose resultst ot he evidencep resented for the corresponding species on the surface and in the near surface region, allowing us to reach ac onsistent picture.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, identifying reactivity of surface adsorbates/intermediates is the key to understand the reaction mechanism of catalytic reactions and establish the structure-performance relation of solid catalysts, both of which are important for rational structural design of efficient catalysts. Surface science studies of model catalysts with uniform and well-defined structures is a widely-used strategy to investigate reactivity of surface adsorbates/intermediates [1,2] due to the structural complexity of powder catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report and later generalization by Tauster et al, the strong metal–support interaction (SMSI), which refers to the high-temperature reduction-induced encapsulation of supported metal nanoparticles by support overlayers, , has become one of the most important concepts in heterogeneous catalysis and has attracted great interest and attention. Extensive studies have focused on the exploration of novel systems exhibiting the SMSI, extending from traditional reducible oxide-supported VIII group metals , to oxide- and non-oxide-supported Au nanoparticles, while there are fewer fundamental studies which have been mainly carried out using model catalysts with well-defined structures. …”
mentioning
confidence: 99%